Analisis Penyebab Anak Putus Sekolah di Desa Lawe Sagu Hilir Kecamatan Lawe Bulan Kabupaten Aceh Tenggara - Mustika, Mentari; Srimulyani, Eka (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Abstract Children are the foundation for the emergence of a new generation that serves as the successors to the nation's aspirations and as human resources for national development. Children are the nation's valuable assets. Educating children is one of the primary responsibilities of parents. Parents are obligated to send their children to school up to the senior high school level, as is the state. However, many children still drop out of school. The aim of this study is to identify the causes of school dropouts in Lawe Sagu Hilir Village, Lawe Bulan Subdistrict, Southeast Aceh Regency. This research employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The findings of this study reveal that the primary causes of school dropouts in Lawe Sagu Hilir Village, Lawe Bulan Subdistrict, Southeast Aceh Regency, are the lack of interest among children in learning and continuing their education. Additionally, economic conditions significantly contribute to this issue, as many parents are unable to afford higher education for their children